Single-cell analysis reveals new subset markers of murine peritoneal macrophages and highlights macrophage dynamics upon Staphylococcus aureus peritonitis. Issue 5 (July 2016) - Accarias, Solène; Genthon, Clémence; Rengel, David; Boullier, Séverine; Foucras, Gilles; Tabouret, Guillaume
Resident macrophages play a central role in maintaining tissue homeostasis and immune surveillance. Here, we used single cell-based qPCR coupled with flow cytometry analysis to further define the phenotypes of large and small resident peritoneal macrophages (LPMs and SPMs, respectively) in mice. We demonstrated that the expression of Cxcl13, IfngR1, Fizz-1 and Mrc-1 clearly distinguished between LPMs and SPMs subsets. Using these markers, the dynamics of peritoneal macrophages in a Staphylococcus aureus -induced peritonitis model were analyzed. We found that S. aureus infection triggers a massive macrophage disappearance reaction in both subsets. Thereafter, inflammatory monocytes rapidly infiltrated the cavity and differentiated to replenish the SPMs. Although phenotypically indistinguishable from resident SPMs by flow cytometry, newly recruited SPMs had a different pattern of gene expression dominated by M2 markers combined with M1 associated features (inos expression). Interestingly, S. aureus elicited SPMs showed a robust expression of Cxcl13, suggesting that these cells may endorse the role of depleted LPMs and contribute to restoring peritoneal homeostasis. These data provide information on both resident and recruited macrophages dynamics upon S. aureus infection and demonstrate that single-cell phenotyping is a promising and highly valuable approach to unraveling macrophage diversity and plasticity.